Design Criterion of Damper Component of Passive-Type Mount Module without Using Base Mass-Block - Chan-Jung Kim (Energies, 2018)
Passive-type mount modules have been used frequently to isolate excitation from the target mechanical system, and electric power plants use the mount devices to control the harmonic excitation source from a combustion engine. The mount structure is composed of a spring component, a stacked thin-panel, and a heavy base-mass block, and installation as well as maintenance of the structures are difficult. To tackle this problem associated with mount modules, I investigate in this work the feasibility of a simplified mount module with no base mass-block; the harmonic frequency of interest was selected from 30 (Hz) to 120 (Hz) owing to the constant rotating speed of the combustion engine at 1800 (rev/min). The design criterion of the damper components was formulated from the response index at the electric power plant, and the influence of the damper component at the proposed mount was calculated theoretically from the linearized system models. The theoretical result was compared with the measured response index at the electric power plant, and the comparison result revealed the superior capability of the proposed mount module in controlling the reaction motion at the electric power plant.